Molecular characterization of organoids derived from pancreatic intraductal papillary mucinous neoplasms. Issue 3 (19th September 2020) - Huang, Bo; Trujillo, Maria A; Fujikura, Kohei; Qiu, Miaozhen; Chen, Fei; Felsenstein, Matthäus; Zhou, Cancan; Skaro, Michael; Gauthier, Christian; Macgregor‐Das, Anne; Hutchings, Danielle; Hong, Seung‐Mo; et al.
Abstract: Intraductal papillary mucinous neoplasms (IPMNs) are commonly identified non‐invasive cyst‐forming pancreatic neoplasms with the potential to progress into invasive pancreatic adenocarcinoma. There are few in vitro models with which to study the biology of IPMNs and their progression to invasive carcinoma. Therefore, we generated a living biobank of organoids from seven normal pancreatic ducts and ten IPMNs. We characterized eight IPMN organoid samples using whole genome sequencing and characterized five IPMN organoids and seven normal pancreatic duct organoids using transcriptome sequencing. We identified an average of 11, 344 somatic mutations in the genomes of organoids derived from IPMNs, with one sample harboring 61, 537 somatic mutations enriched for T→C transitions and T→A transversions. Recurrent coding somatic mutations were identified in 15 genes, including KRAS, GNAS, RNF43, PHF3, and RBM10 . The most frequently mutated genes were KRAS, GNAS, and RNF43, with somatic mutations identified in six (75%), four (50%), and three (37.5%) IPMN organoid samples, respectively. On average, we identified 36 structural variants in IPMN derived organoids, and none had an unstable phenotype (> 200 structural variants). Transcriptome sequencing identified 28 genes differentially expressed between normal pancreatic duct organoid and IPMN organoid samples. The most significantly upregulated and downregulated genes were CLDN18 and FOXA1 . Immunohistochemical analysis of FOXA1 expression in 112 IPMNs, 113 mucinous cystic neoplasms, and 145 pancreatic ductal adenocarcinomas demonstrated statistically significant loss of expression in low‐grade IPMNs ( p  < 0.0016), mucinous cystic neoplasms ( p  < 0.0001), and pancreatic ductal adenocarcinoma of any histologic grade ( p  < 0.0001) compared to normal pancreatic ducts. These data indicate that FOXA1 loss of expression occurs early in pancreatic tumorigenesis. Our study highlights the utility of organoid culture to study the genetics and biology of normal pancreatic duct and IPMNs. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.